A Sociological Study of Hikikomori - Matsushita, Yuki; Yasumatsu, Nori (Journal of Humanities and Social Sciences (JHASS), 2025)
Hikikomori, a term used to describe individuals who experience severe social withdrawal, has become an increasingly prominent social issue in Japan. This phenomenon, once considered an isolated occurrence, now affects a growing number of individuals, particularly among young people, with profound social, psychological, and economic consequences. The aim of this study is to investigate the underlying causes of hikikomori, its psychological and societal impacts, and the effectiveness of current interventions. A mixed-methods approach was employed, combining qualitative case studies and quantitative surveys to examine the factors contributing to social isolation, including societal pressures, family dynamics, and the role of technology. The findings reveal that academic stress, unemployment, and changing family structures are significant contributors to hikikomori. Furthermore, the study highlights the psychological toll on affected individuals, including depression, anxiety, and low self-esteem, as well as the strain on family members and social systems. While current interventions, such as counseling services and government programs, show some promise, they are often insufficient in addressing the root causes of the issue. This study concludes that hikikomori is not only a personal issue but a societal challenge that requires comprehensive, multi-faceted interventions. Future research should focus on exploring more effective support systems, the role of technology in exacerbating isolation, and the long-term impact of hikikomori on Japan's workforce and economy.